Chemical Fingerprint Assessment of Surface Resistance in Silicone Rubber Insulators Using Coal Fly Ash as Filler - Harjib Haridh; Syamsir Abduh; Christiono Christiono (Sultan Publisher, 2026)
To support the infrastructure targets of Indonesia's PLN Electricity Supply Business Plan (RUPTL) 2025–2034 while managing abundant coal fly ash waste, this study investigates CFA valorization as a functional filler in silicone rubber insulators. Addressing the need for sustainable grid expansion, the research primarily focuses on the relationship between FTIR-derived chemical descriptors, CFA composition, and composite surface resistance. Chemical fingerprinting analysis demonstrates that CFA with high SiO₂ content (42.0%) better supports the composite's siloxane networks compared to iron-rich variants. Statistical modeling (adjusted R² > 0.92) confirms filler concentration as the primary predictor of resistance (p < 0.001). Optimal structural stability was associated with a 2:1 stoichiometric ratio of dimethyl groups—directly attached to the central silicon atoms (Si(CH₃)₂)—relative to the Si-O-Si backbone. Furthermore, a critical percolation threshold was identified at 70% filler concentration, beyond this loading level the integrity of the fundamental PDMS polymer structure is compromised, resulting in deteriorated insulator performance. These findings suggest that FTIR-based chemical fingerprinting has the potential to serve as an effective quality control framework, offering a scientifically grounded, sustainable material alternative in direct alignment with RUPTL strategic objectives.